THE HARDWARE SYSTEMS MODERNIZATION OF AUTO-TRACKING OF HIGH-SPEED MOVING OBJECTS - Yuri Valerievich Ilyushin; Dmitry Anatolyevich Pervukhin; Ivan Mitrofanovich Pershin (Современная наука и инновации)
The article deals with the organization of a parallel method for guidance as a way of increasing the effectiveness of anti-missile defense. The paper presents the developed block diagram pointing missiles at an enemy missile. Block diagram of the algorithm implements a parallel guidance for the implementation of which has been established on the basis of chip ALU 741811, as presented in this article. The article also report concluded further ways of development of these techniques.